The Influence of Local Culture on English Code-Mixing Social Media - Rosalina, Afni - (Universitas Harapan Medan, 2025)
This research aims to analyze the influence of local culture on English code-mixing practices on social media, particularly among young users in Indonesia. Using critical discourse analysis, the study examines digital texts (captions, comments, and posts) collected from platforms such as Instagram, Twitter, and TikTok. The findings suggest that local cultural aspects such as traditional meals, local holidays, regional languages, and popular cultural symbols regularly occur in code-mixing behaviors. Code-mixing is employed not only as a current communication style but also as a type of global (global and local) cultural identity manifestation. These findings show that local culture remains significant in the digital and global era and has a role in shaping the communication habits of future generations.